COHERENCE BETWEEN OBJECTIVE AND TEACHING / LEARNING STRATEGY (CIPEEX, 2022)
IN EDUCATION, DECIDING AND DEFINING LEARNING OBJECTIVES MEANS CONSCIOUSLY STRUCTURING THE EDUCATIONAL PROCESS TO ALLOW FOR CHANGES IN THOUGHTS, ACTIONS AND BEHAVIORS, ENCOMPASSING COGNITIVE, AFFECTIVE, ATTITUDINAL, PSYCHOMOTOR AND COMPETENCE ASPECTS. THE STRUCTURING OF OBJECTIVES MUST BE THE RESULT OF A PLANNING PROCESS DIRECTLY LINKED TO THE CHOICE OF CONTENT AND STRATEGY TO BE ADOPTED FOR A CERTAIN PERIOD OF TIME. THE COHERENCE BETWEEN THE OBJECTIVES AND THE STRATEGIES OF TEACHING LEARNING IS VERY IMPORTANT SO THAT THE STUDENT AND THE TEACHER UNDERSTAND THE WAY TO BE TRAVELED AND WHERE THEY SHOULD ARRIVE, GUARANTEEING AN EFFECTIVE TEACHING / LEARNING PROCESS. THEREFORE, THE OBJECTIVE OF THIS STUDY IS TO DISCUSS THE USE OF TEACHING / LEARNING STRATEGIES TO ACHIEVE THE COGNITIVE DOMAIN OF CONTENT. THE COGNITIVE DOMAIN INVOLVES THE ACQUISITION OF NEW KNOWLEDGE, INTELLECTUAL DEVELOPMENT, SKILL AND NEW ATTITUDES. BLOOM ET AL. (1956) DESCRIBED CATEGORIES OF THE COGNITIVE DOMAIN THAT ENCOMPASS KNOWLEDGE, COMPREHENSION, APPLICATION, ANALYSIS, SYNTHESIS AND, FINALLY, EVALUATION. IN ORDER FOR THE PROCESS OF TEACHING LEARNING TO BE SUCCESSFUL ALL THESE CATEGORIES MUST BE PRESENT IN THE DEFINITION OF THE OBJECTIVES OF THE PROGRAMMATIC CONTENTS AND ALIGNED TO THE STRATEGIES OF TEACHING LEARNING. WHEN LEARNING OBJECTIVES PERMEATE THE KNOWLEDGE CATEGORY, BRAINSTORMING CAN BE PLANNED TO FOSTER THE MEANINGFUL LEARNING OF DAVID AUSUBEL, WHO SAYS THAT "THE SINGLE MOST IMPORTANT FACTOR INFLUENCING LEARNING IS WHAT THE LEARNER ALREADY KNOWS" , THE DIALOGIC EXPOSITIVE CLASS THAT MEDIATES, ORGANIZES, CLARIFIES AND GUIDES THE STUDY OF CONTENT AND VIDEO LESSONS. IN THE UNDERSTANDING CATEGORY ONE CAN WORK WITH GUIDED STUDIES, TEXT STUDIES, PORTFOLIOS, PANEL, STUDY OF MEANS, FORUM OF DISCUSSION, AMONG OTHERS. FOR THE APPLICATION OF KNOWLEDGE, THE TEACHER CAN USE STRATEGIES SUCH AS SEMINARS, VERBALIZATION AND OBSERVATION GROUP (GVGO), SYMPOSIUMS, WORKSHOPS, PHILLIPS 66, AMONG OTHERS. FOR CATEGORY ANALYSIS THE USE OF PROBLEM SOLVING, PBL, PROBLEMATIZATION, CASE STUDY, JURY SIMULATION, FORUM OF DISCUSSIONS AND RESEARCH IS PROPOSED. FOR THE SYNTHESIS OF KNOWLEDGE ONE CAN USE CONCEPTUAL MAPS, CONTENT RESUMES, MENTAL MAPPING, SEMINARS, TBL AND MORE. AND THE EVALUATION OF CONTENT LEARNING CAN BE PERFORMED PROCEDURALLY WITH THE ASSIGNMENT OF VALUES €‹€‹TO ALL THESE STRATEGIES ASSOCIATED WITH THEORETICAL AND PRACTICAL EVALUATIONS OF CONTENT. IT SHOULD BE EMPHASIZED THAT THE STRATEGIES ARRANGED IN EACH BLOOM COGNITIVE DOMAIN CATEGORY ARE NOT FIXED AND CAN BE ASSOCIATED TO ACHIEVE EFFECTIVE LEARNING, AS WELL AS THE USE OF COMMUNICATION AND INFORMATION TECHNOLOGIES THAT, WHEN WELL PLANNED, FIT INTO ALL CATEGORIES OF BLOMM.
Keywords: Teaching and learning strategies. Teaching objectives. Taxonomy of Bloom.